Analysis of the football players’ actual nutrition - E. E. Keshabyants; N. N. Denisova; E. Yu. Sorokina; R. M. Radzhabkadiev; K. V. Vybornaya (Спортивная медицина: наука и практика, 2021)
Objective: to assess the actual nutrition of football players according to their personal daily energy expenditures.Materials and methods: the study of the actual nutrition of the athletes of the division II football team was carried out at the training camp. A total of 23 athletes participated in this study, including 3 goalkeepers, 3 attackers, 7 defenders, and 10 midfielders. The average age of the team is 24.2 ± 0.3 years. The collection of information on actual nutrition was carried out in two ways: using a 24-hour dietary recall method for at least 2 days and frequency meal analysis method. The amount of food consumed was determined using lists that include information on portions and meals. The chemical composition and energy value of the diets were evaluated using two databases of Russian food composition tables. Energy expenditures were calculated using the heart rate monitoring.Results: study results show that the energy value of football players’daily ration averaged 2560.6 ± 150.6 kcal, while the average energy expenditure was 4100.0 ± 51.3 kcal/day. The study revealed high levels of fat (42 %) and EFA (14,8 %) consumption in terms of dietary intake, while the proportion of energy from carbohydrates was insufficient, only 43.1 %. Moreover, the athletes obtain 17.5 % of their energy intake from added sugar. In addition, the study revealed insufficient intake of vitamins A and B1 among 86 % of athletes, B2 — 79 %, niacin — 65 % and vitamin C — 72 %. Analysis of the daily intake of minerals revealed an insufficient calcium content in the 38 % of football players’ diets, magnesium — in 62 %, and low calcium to phosphorus ratio — in 44 % of diets.Conclusion: the data obtained showed a nutritional imbalance of the football players, both in intake of calories and in the nutrient consumption. 50 % of the athletes surveyed have insufficient protein intake, 80 % of those surveyed had high levels of fat and EFA consumption. The study revealed a high prevalence of genetic polymorphism associated with impaired bone mineralization. Considering that high performance sport requires a special approach to each athlete, taking into account his individual needs, the functional state of the body, genetic characteristics, the training phases, each athlete needs a personal diet, which will include certain products, vitamin and mineral supplements, and will definitely be adjusted in the future.